2018
DOI: 10.6001/actamedica.v25i2.3760
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation of late preterm infants due to lower respiratory tract infections in Lithuania, Latvia, and Estonia: incidence, disease severity, and risk factors

Abstract: Background.By two years of age, almost all children experience at least one episode of respiratory syncytial virus (RSV) infection, the most common viral cause of hospitalisation due to lower respiratory tract infection (LRTI). We present data on LRTI hospitalisations (with a special focus on RSV), the course of illness, and LRTI hospitalisation risk factors in Lithuania, Latvia, and Estonia.Materials and methods.The analysed data were part of a large multinational study conducted in 23 countries (PONI). LRTI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
1
1
2
Order By: Relevance
“…In contrast with the findings of the present study, a significant association between hospitalization caused by lower respiratory tract disease, male gender, maternal age lower than 25 years, and dependence on oxygen after birth was found ( 21 ) . A prospective cohort study ( 22 ) showed similar average maternal age; however, variables such as maternal age and level of education and existence of siblings with acute respiratory infection showed no association with hospitalization, similar to what was found in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with the findings of the present study, a significant association between hospitalization caused by lower respiratory tract disease, male gender, maternal age lower than 25 years, and dependence on oxygen after birth was found ( 21 ) . A prospective cohort study ( 22 ) showed similar average maternal age; however, variables such as maternal age and level of education and existence of siblings with acute respiratory infection showed no association with hospitalization, similar to what was found in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Babies with GA from 33 to 34 weeks showed a hospitalization rate twice as high as that observed for newborns with GA superior to 35 weeks. A study in Eastern Europe ( 21 ) showed that, within the virus season, the incidence of hospitalizations of late preterm infants caused by lower respiratory tract diseases was 6.5%, whereas the number for lower respiratory tract infections caused by RSV was 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Das variáveis maternas, em contraste com os achados desse estudo, investigação (21) encontrou associação significativa entre hospitalização por DTRI e sexo masculino, idade materna menor que 25 anos e dependência de oxigênio após nascimento. Em uma coorte prospectiva (22) , a média de idade materna foi semelhante; contudo, variáveis como idade e escolaridade maternas e presença de irmãos com IRA não apresentaram associação e ratificam os resultados aqui apresentados.…”
Section: Discussionunclassified
“…Bebês com IG de 33 a 34 semanas, ao nascer, demonstraram duas vezes mais internações que bebês com IG superior a 35 semanas (5) . Estudo (21) no leste europeu revelou que, dentro do período sazonal do vírus, a incidência de hospitalizações de prematuros tardios em razão de DTRI foi de 6,5% e para DTRI em razão do VSR foi de 1,7%.…”
Section: Discussionunclassified